2010
DOI: 10.1111/j.1365-2958.2010.07466.x
|View full text |Cite
|
Sign up to set email alerts
|

In Sup35p filaments (the [PSI+] prion), the globular C‐terminal domains are widely offset from the amyloid fibril backbone

Abstract: Summary In yeast cells infected with the [PSI+] prion, Sup35pforms aggregates and its activity in translation termination is downregulated. Transfection experiments have shown that Sup35p filaments assembled in vitro are infectious, suggesting that they reproduce or closely resemble the prion. We have used several EM techniques to study the molecular architecture of filaments, seeking clues as to the mechanism of downregulation. Sup35p has an N-terminal 'prion' domain; a highly charged middle (M-)domain; and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 60 publications
6
36
0
1
Order By: Relevance
“…An alternative explanation for the observed variable spacing is that the apparent separation distance depends on the oblique orientations of the fibrils in these 50-to 80-nm-thick sections. The core fibril diameter was consistent with EM studies of full-length, NM-and N-domain fibrils in vitro, which showed that the middle and Cterminal domains are flexible and can extend considerably from the fibril backbone (49). By analogy, it is likely that the globular GFP domains are also mobile in our fibrils.…”
Section: Nm-gfp Fibrils Do Not Maintain Associations With the Preautosupporting
confidence: 85%
See 1 more Smart Citation
“…An alternative explanation for the observed variable spacing is that the apparent separation distance depends on the oblique orientations of the fibrils in these 50-to 80-nm-thick sections. The core fibril diameter was consistent with EM studies of full-length, NM-and N-domain fibrils in vitro, which showed that the middle and Cterminal domains are flexible and can extend considerably from the fibril backbone (49). By analogy, it is likely that the globular GFP domains are also mobile in our fibrils.…”
Section: Nm-gfp Fibrils Do Not Maintain Associations With the Preautosupporting
confidence: 85%
“…NM fibers have never been observed to form such arrays in vitro (22,27,49,52). Therefore, we reasoned that other cellular factors must dictate the arrangement of the fibril arrays.…”
Section: Discussionmentioning
confidence: 99%
“…Extended and flexible M domains connect the core to the C domains that have enough space to interact with ribosomes (shown to scale). Adapted from Baxa et al (2011). loops. These non-b-sheet loops can account for the residues that are not within the 4.7-Å distance ( Figure 7B).…”
Section: Models Of Prion Structuresmentioning
confidence: 99%
“…The lack of suppression of toxicity by Sup35MC argues against such a burden being caused by possible production of proteins with C-terminal extensions due to the read through of stop codons in [PSI 1 ] cells. Recent data suggest that the globular C termini of the Sup35p monomers within amyloid fibers is accessible to interact with ribosomes, which might explain why the considerable depletion of soluble Sup35p in [PSI 1 ] cells does not reduce growth (Baxa et al 2011). It is possible that a function of the Sis1p CTD facilitates such an interaction.…”
Section: [Psi 1 ] Is Lethal To Cells Expressing Hdj1p In Place Of Sis1pmentioning
confidence: 99%